Appropriate information on local technology - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Vraagbaak, a Dutch periodical on small-scale technology, is published four times a year in Dutch, English and French Vraagbaak is published by the AGROMISA Foundation (Wageningen, The Netherlands)